2007
DOI: 10.1002/ijc.22547
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at XPD and XRCC1 DNA repair loci and increased risk of oral leukoplakia and cancer among NAT2 slow acetylators

Abstract: Polymorphisms at N-acetyl transferase 2 locus (NAT2) lead to slow, intermediate and rapid acetylation properties of the enzyme. Improper acetylation of heterocyclic and aromatic amines, present in tobacco, might cause DNA adduct formation. Generally, DNA repair enzymes remove these adduct to escape malignancy. But, tobacco users carrying susceptible NAT2 and DNA repair loci might be at risk of oral leukoplakia and cancer. In this study, 389 controls, 224 leukoplakia and 310 cancer patients were genotyped at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 23 publications
4
53
1
Order By: Relevance
“…There have been several studies showing associations between this SNP and risk of multiple cancers, including HNC, but the results from different populations were confusing rather than conclusive (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Recently, a meta-analysis with a total of 12 studies claimed that the XPD Lys751Gln polymorphism was not associated with HNC risk (17); however, no genotyping data from the Chinese population was included, with the exception of a Taiwan study with a small sample size of 154 cases and 105 controls (30).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies showing associations between this SNP and risk of multiple cancers, including HNC, but the results from different populations were confusing rather than conclusive (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Recently, a meta-analysis with a total of 12 studies claimed that the XPD Lys751Gln polymorphism was not associated with HNC risk (17); however, no genotyping data from the Chinese population was included, with the exception of a Taiwan study with a small sample size of 154 cases and 105 controls (30).…”
Section: Discussionmentioning
confidence: 99%
“…XRCC1 polymorphisms were first reported as a risk factor for oral cancer (Sturgis et al 1999). Since then, a number of studies have confirmed or refuted this phenomenon (Majumder et al 2005(Majumder et al , 2007Matullo et al 2006;Ramachandran et al 2006;Kietthubthew et al 2006;Ho et al 2007;Yen et al 2008). These disparate findings may be due to insufficient power in some studies, differences between cancer types, type of study populations and study design.…”
mentioning
confidence: 98%
“…In conclusion, our study could provide a preliminary basis for cancer risks assessment that are associated with polymorphisms among these DNA repair genes by (Harithy and Ghazzawi et al 2011); GIH-Gujarati Indians in Houston, Texas; SInd-South Indian population in India (Vettriselvi et al, 2007); NInd-North Indian population in India (Gangwar et al, 2009); EInd-Eastern Indian population from Calcutta, India (Majumder et al, 2007) performing genetic epidemiological studies in the Deccan region population of India. Furthermore, our results indicate a distinct molecular profile of polymorphisms for the DNA repair genes XRCC1, XRCC3, OGG1 and XPD loci for HYB compared to other populations.…”
Section: Discussionmentioning
confidence: 81%
“…The CHB, JPT, YRI, MKK, and GIH populations differed significantly with HYB population based on Pairwise Chi-square (χ 2 ) ( Table 4). (Harithy and Ghazzawi et al 2011); GIH-Gujarati Indians in Houston, Texas; SInd-South Indian population in India (Vettriselvi et al, 2007); NInd-North Indian population in India (Gangwar et al, 2009); EInd-Eastern Indian population from Calcutta, India (Majumder et al, 2007); MAH-Maharashtrian population residing in Vidarbha region of central India; HYB-Hyderabad population residing in Deccan region of South India; a Chi-square test statistic value less than 3.841 at 5% significance level, so populations are not significantly different from HYB (92) 0.66 (188) 0.021 (6) …”
Section: A L L E L E a N D G E N O T Y P E F Re Q U E N C I E S O F Xmentioning
confidence: 99%